"Strategies for Closing Three Major Gender Gaps: Participation/Engagement Gap, Pay Gap and Advancement/ Leadership Gap". Presentation/report gender IT Conference: Women Choosing ICT Careers: Influencing Policy from Practice, HAU, Athens, Greece - Irene Kamberidou (Fostering Gender Mainstreaming in the ICT Sector, E-Newsletter, pp. 1-5. Also in: http://www.gender-it.eu and in http://www.ictwomendirectory.eu/digitalcity/projects/eudir/eudir_news., 2010)
Encouraging more women and girls to take up ICT, retaining them in the sector and reproducing female participation requires working together to support an “Education-Engagement-Retention Action Plan”  (Kamberidou 2008) that entails: (1) Support of multicultural interdisciplinary gender research networks and collaborative actions that address the three major gender gaps:(a) the gender participation/engagement gap, (b) the pay gap and the (c) advancement-leadership gap. (2) Support of multicultural interdisciplinary gender research to influences mainstream developments in science and technology from a gender perspective, including a better balance of gendered content to change attitudes, perceptions and stereotypes. (3) Interdisciplinarity in education and research in order to formulate new pedagogical methods and approaches that incorporate the gender dimension. Education-training and engagement for teachers and children means extra-curricula approaches, new classroom examples and best practice models. (3) Educating the educators, re-training the trainers: learning, continued training and re-training. (4) Participation in areas of planning, management, assessment and organization. (5) Family support programmes, flexi-hours, a family-friendly working environment, child care facilities, namely an inclusive work culture. (6) The establishment of an attractive open labour market that recruits and retains women. (7) Gender networking, alliances with women, sharing, mentoring and supporting younger female colleagues in order to eliminate “gender fatigue” (Kamberidou 2010) and encourage women to take a more active role (agency), to keep up with developments, to share information, etc. (8) Social mobility in the structure, i.e. learning the system and how to use it in order to make changes. (9) Best-practice models and mentoring projects: the involvement of professional women (Leaders) already employed in science and technology, the academia, research sectors. (10)  Raising the profile of our role models and female leaders as well as the diversity of careers available. We need to inspire women into technology with innovative and different approaches such as the European Commission’s shadowing activities (http://ec.europa.eu/itgirls, mentoring programs and so forth. We need to all join forces and work together to accomplish this. For example, the ECWT (www.womenandtechnology.eu) and the EUD www.ictwomendirectory.eu)  provide such a platform for collaborations. Disseminated to 5.000 readers in five languages (translated from English), Greek translation G.3.1 in Apella. Κυκλοφόρησε αρχικά σε e-Newsletter το οποίο μεταφράστηκε σε πέντε (5) γλώσσες και διανεμήθηκε ηλεκτρονικά σε 5.000 αναγνώστες (Fostering Gender Mainstreaming in the ICT Sector, E-Newsletter, Nov. 19, 2010, pp. 1-5)  Η προαναφερόμενη εισήγηση δημοσιεύτηκε ηλεκτρονικά μετά το συνέδριο (στο πλαίσιο του Ευρωπαϊκού συνεδρίου:  “Women Choosing ICT careers: Influencing Policy from Practice.” Που πραγματοποιήθηκε στο Hellenic American Union, Athens Greece, 26 Οκτ. 2010. (ζωντανή μετάδοση του συνεδρίου at http://www.ustream.tv/channel/gender-it-conference. Αναδημοσίευση του προαναφερόμενου άρθρου στις ιστοσελίδες των e-news  του ECWT-European Centre for Women and Technology (www.womenandtechnology.eu) και στο   http://www.ictwomendirectory.eu/digitalcity/projects/eudir/eudir_news-